Usual Interstitial Pneumonia and Non-Specific Interstitial Pneumonia: Serial Thin-Section CT Findings Correlated with Pulmonary Function - Jeong, Yeon Joo (The Korean Radiological Society, 2005)
OBJECTIVE: We wanted to demonstrate and compare the serial high-resolution CTs (HRCT) and the pulmonary function test (PFT) findings of the usual interstitial pneumonia (UIP) and the non-specific interstitial pneumonia (NSIP). MATERIALS AND METHODS: The serial HRCT scans and the PFT results were retrospectively analysed and compared for 35 patients having UIP without significant honeycombing (UIP-w/o hc, < 5% of honeycombing at CT), 35 patients having UIP with honeycombing (UIP-w/i hc, ≥ 5% of honeycombing), and 25 patients with NSIP. The mortality rates were also compared. Follow-up CT scans were available in 75 patients (29 UIP-w/o hc patients, 22 UIP-w/i hc patients and 24 NSIP patients) and the follow-up periods ranged from 150 to 2,370 days. The initial and follow-up PFT data were available for 71 patients. RESULTS: On the initial CT, significant differences were present between the UIP-w/i hc patients and both the UIP-w/o hc patients and the NSIP patients in the overall extent, ground-glass opacity (GGO) away from the reticulation, reticulation and honeycombing (all p < 0.05). Improvement was noticed in five (17%) of 29 UIP-w/o hc patients, none of 22 UIP-w/i hc patients, and 9 (37%) of 24 NSIP patients; deterioration was noted in six (21%) UIP-w/o hc patients, two (9%) UIP-w/i hc patients and three (13%) NSIP patients (p = 0.044 between UIP-w/o and UIP-w/i hc; p = 0.637 between UIP-w/o hc and NSIP; p = 0.007 between UIP-w/i hc and NSIP). The serial changes of the pulmonary function in the NSIP patients were different from those noted for the UIP-w/i hc and UIP-w/o hc patients (p = 0.440 between UIP-w/o and UIP-w/i hc; p = 0.022 between UIP-w/o hc and NSIP; p = 0.003 between UIP-w/i hc and NSIP). Five (14%) of the 35 patients with UIP-w/o hc, 16 (46%) of the 35 patients with UIP-w/i hc and three (12%) of the 25 patients with NSIP died (p = 0.002, comparison for the three groups). CONCLUSION: On CT, NSIP and UIP-w/o hc patients have similar patterns of parenchymal abnormalities and a similar likelihood of change in the extent of disease on follow-up. Patients with UIP-w/i hc have distinctive features and a worst prognosis.